2019
DOI: 10.1149/2.0121910jes
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Electrolyte Quantity on Lithium-Ion Cells

Abstract: In the production process chain of lithium-ion battery cells, the filling process is eminent for the final product quality and costs. The filling consists of several dosing steps of electrolyte liquid into the cell and the subsequent (intermediate) wetting of the cell components. The quantity of electrolyte filled not only has an impact on the wetting rate of electrodes and separator but also limits the capacity of the cell and influences the battery lifetime. However, too much electrolyte is dead weight, resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 32 publications
2
79
0
Order By: Relevance
“…For conventional LIBs, the liquid electrolyte is injected into the cell to fill the pores in the electrodes and the separator. The process is decisive for the overall cell quality and the subsequent wetting can be a bottleneck in cell production …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For conventional LIBs, the liquid electrolyte is injected into the cell to fill the pores in the electrodes and the separator. The process is decisive for the overall cell quality and the subsequent wetting can be a bottleneck in cell production …”
Section: Methodsmentioning
confidence: 99%
“…Electrolyte Filling and Riveting: For conventional LIBs, the liquid electrolyte is injected into the cell to fill the pores in the electrodes and the separator. The process is decisive for the overall cell quality [36,66] and the subsequent wetting can be a bottleneck in cell production. [67] Formation: During the formation procedure, the cells are charged for the first time.…”
Section: Baseline Parametersmentioning
confidence: 99%
“…[ 181 ] Please note that excess electrolyte does not support lithium‐ion storage capacity, but adds weight of inactive components to the cell, which leads to a reduction in energy density. [ 182 ] Hence, especially for application‐oriented cells, an optimized amount of electrolyte regarding energy density should be determined (although varied amounts of electrolyte might be optimal for other quality parameters). [ 179 ] Therefore, a direct comparison of the electrolyte‐filling process and its impact on cell performance for lab‐made and industrially produced cells is limited.…”
Section: Challenges In the Upscaling Of Battery Cell Productionmentioning
confidence: 99%
“…[ 148 ] By varying the volumetric factors of electrolyte or the electrolyte quantity, the capacity and capacity retention of lithium‐ion batteries were investigated (as shown in Figure 20d). [ 149 ] It was found that too little electrolyte leads to a loss of capacity and lifetime, whereas too much electrolyte reduces the energy density. If there is a lack of electrolyte, the voltage drops sharply already at the beginning of the discharging process.…”
Section: Transforming Materials Into Practicalmentioning
confidence: 99%
“…HFR and EIS might be good tools to detect the redistribution of the electrolyte within the pores. [ 149 ]…”
Section: Transforming Materials Into Practicalmentioning
confidence: 99%